Embedding a Sensitive Liquid-Core Waveguide UV Detector into an HPLC-UV System for Simultaneous Quantification of Differently Dosed Active Ingredients during Drug Release - Rebecca Chamberlain; Hellen Windolf; Bjoern B. Burckhardt; Jörg Breitkreutz; Björn Fischer (MDPI AG, 2022)
Individual dosing of pharmaceutics and personalized medicine have become important with regard to therapeutic safety. Dose adjustments, biorelevant drug release and combination of multiple active substances in one dosage form for the reduction in polymedication are essential aspects that increase the safety and acceptance of the patient's pharmacotherapy. Therefore, not only innovative drug products but also new analytical methods are needed during the drug development phase and for quality control that can simultaneously determine different active ingredients and cover wide concentration ranges. We investigated a liquid-core waveguide UV absorbance flow cell detector coupled to an existing HPLC-UV system. A Teflon AF 2400 capillary tubing of 20 cm length was connected in series to the HPLC flow line and enabled a lower limit of quantification of 1 ng/mL pramipexole (increase in sensitivity by 20 compared to common 0.9 cm flow cells). This allowed the low-concentration of pramipexole and the higher concentrations of levodopa and benserazide occurring during drug release to be determined in a single chromatographic run within 22.5 min.